Aquarium: open-source laboratory software for design, execution and data management. Issue 1 (30th January 2021) - Vrana, Justin; de Lange, Orlando; Yang, Yaoyu; Newman, Garrett; Saleem, Ayesha; Miller, Abraham; Cordray, Cameron; Halabiya, Samer; Parks, Michelle; Lopez, Eriberto; Goldberg, Sarah; Keller, Benjamin; et al.
Abstract: Automation has been shown to improve the replicability and scalability of biomedical and bioindustrial research. Although the work performed in many labs is repetitive and can be standardized, few academic labs can afford the time and money required to automate their workflows with robotics. We propose that human-in-the-loop automation can fill this critical gap. To this end, we present Aquarium, an open-source, web-based software application that integrates experimental design, inventory management, protocol execution and data capture. We provide a high-level view of how researchers can install Aquarium and use it in their own labs. We discuss the impacts of the Aquarium on working practices, use in biofoundries and opportunities it affords for collaboration and education in life science laboratory research and manufacture.